SOMATIC EMBRYOGENESIS AND PLANT REGENERATION FROM AN ELITE TROPICAL MAIZE INBRED LINE - SOUZA, RAFAELI APARECIDA VIEIRA DE; ALVES, MEIRE DE CÁSSIA; CARNEIRO, NEWTON PORTILHO; BORÉM, ALUÍZIO; CARNEIRO, ANDRÉA ALMEIDA (International Journal of Maize & Sorghum, 2016)
ABSTRACT – The improvement of tropical maize inbred lines by genetic transformation techniques remains a difficult task since not all genotypes are capable of regenerating efficiently in vitro. The objective of this study was to evaluate three different callus induction media, based on N6 or MS salts containing either 2,4-D (0, 2.5, 5.0, 10.0, 15.0, 30.0 mg .L-1) or Dicamba (0; 0.25; 0.5; 1.0; 2.0; 4.0 mg.l-1) in the production of embryogenic callus from immature zygotic embryos of the tropical maize inbred line L3. Callus maturation was tested in MS medium containing 60 g.L-1 sucrose and supplemented with different combinations of BAP (0; 0.1; 0.5; 1.0 mg.L-1), NAA (0; 1.0 mg.L-1) and CuSO4 (0; 1.25 mg.L-1). The L3 inbred line presented higher capacity for Type II callus formation on N6 medium content 10 mg.L-1 2,4-D. For the maturation of callus, absence of plant growth regulators and addition of CuSO4 allowed higher percentage of regeneration. The protocol developed presented 85% production of Type II embryogenic callus and 45% plant regeneration. Keywords: 2,4-D, dicamba, embryogenic callus, Zea mays. EMBRIOGÊNESE SOMÁTICA E REGENERAÇÃO DE PLANTAS A PARTIR DE UMA LINHAGEM DE MILHO TROPICAL ELITE RESUMO – O melhoramento de linhagens de milho tropical através de técnicas de transformação genética continua a ser uma tarefa difícil uma vez que nem todos os genótipos são capazes de regenerar eficientemente in vitro. O objetivo deste estudo foi avaliar três meios diferentes para a indução de calos embriogênicos, baseados em N6 ou MS sais contendo 2,4-D (0; 2,5; 5,0; 10,0; 15,0; 30,0 mg.L-1) ou Dicamba (0; 0,25 ; 0,5; 1,0; 2,0; 4,0 mg.l-1) na produção de calos embriogênicos a partir de embriões zigóticos imaturos da linhagem de milho tropical elite L3. A maturação dos calos foi testada em meio MS com 60 g.L-1 de sacarose suplementado com diferentes combinações de BAP (0; 0,1; 0,5; 1,0 mg.L-1), ANA (0; 1,0 mg.L-1) e CuSO4 (0; 1,25 mg L-1). A linhagem L3 apresentou alta capacidade para produção de calos do Tipo II em meio N6 contendo 10 mg.L-1 de 2,4-D. Para a maturação dos calos, ausência de reguladores de crescimento vegetal e adição de CuSO4 possibilitou maior porcentagem de regeneração. O protocolo desenvolvido apresenta produção de 85% de calos embriogênicos do Tipo II e 45% de regeneração de plantas. Palavras-chave: 2,4-D, dicamba, calos embriogênicos, Zea mays <!–[endif] –>